Probing scalar effective field theories with the soft limits of scattering amplitudes - Padilla, Antonio; Stefanyszyn, David; Wilson, Toby (Springer, 2017)
We investigate the soft behaviour of scalar effective field theories (EFTs) when there is a number of distinct derivative power counting parameters, ρ1 < ρ2 < . . . < ρQ. We clarify the notion of an enhanced soft limit and use these to extend the scope of onshell recursion techniques for scalar EFTs. As an example, we perform a detailed study of theories with two power counting parameters, ρ1 = 1 and ρ2 = 2, that include the shift symmetric generalised galileons. We demonstrate that the minimally enhanced soft limit uniquely picks out the Dirac-Born-Infeld (DBI) symmetry, including DBI galileons. For the exceptional soft limit we uniquely pick out the special galileon within the class of theories under investigation. We study the DBI galileon amplitudes more closely, verifying the validity of the recursion techniques in generating the six point amplitude, and explicitly demonstrating the invariance of all amplitudes under DBI galileon duality.